Evaluation of changes in microbial populations on beef carcasses resulting from steam pasteurization - Brown, T.L.; Peters, P.E.; Kropf, Donald H.; Phebus, Randall K.; Nutsch, Abbey L.; Kastner, Curtis L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
The steam pasteurization process (SPS 400) developed by Frigoscandia Food Process Systems (Bellevue, WA) was effective in reducing bacterial populations in both laboratory and commercial settings. The objective of steam pasteurization and other meat decontamination measures is to extend product shelf life and improve safety by inhibiting or inactivating pathogens, while at the same time maintaining acceptable meat quality characteristics. The effects of steam pasteurization on beef carcass bacterial populations were evaluated at two large commercial beef processing facilities. A shelf-life study also was conducted to determine the microbial profiles of vacuum packaged beef loins from pasteurized and non-pasteurized carcasses. Steam pasteurization greatly reduced total beef carcass bacterial populations and was most effective in reducing gram negative organisms, including potential enteric pathogens of fecal origin. Thus, the relative percentage of gram positive microflora on beef carcass surfaces, especially Bacillus spp. and Staphylococcus spp., increased.
Keywords: Beef; Steam pasteurization; Microbial; Populations; Carcasses